A re‐innervated in vitro skin model of non‐histaminergic itch and skin neurogenic inflammation: PAR2‐, TRPV1‐ and TRPA1‐agonist induced functionality - N. Lebonvallet; J. W. Fluhr; C. Le Gall‐Ianotto; R. Leschiera; M. Talagas; A. Reux; A. Bataille; C. Brun; T. Oddos; J.‐P. Pennec; J.‐L. Carré; L. Misery (Wiley, 2021)
Abstract Background Skin, and epidermis, is innervated by sensory nerve fibres. Interactions between them and signal transduction are only partially elucidated in physiological/pathological conditions, especially in pruritus. Objectives To study the mechanisms involved in pruritus in vitro, we developed a skin explant model re‐innervated by sensory neurons. Methods This model is based on the co‐culture of human skin explants and sensory neurons from dorsal root ganglia of rats. Innervation and the expression of protease activated receptor 2 (PAR2), transient receptor potential vanilloid 1 (TRPV1) and transient receptor potential ankyrin one (TRPA1) was analysed by immunostaining. The response of the model to TRPV1, PAR2 and TRPA1 agonists was analysed by patch‐clamp, qPCR and enzyme‐linked immunosorbent assay. Results After 5 days of re‐innervating nerve fibres was evidenced in the epidermis. Re‐innervation was correlated with decrease of epidermal thickness and the number of apoptotic cells in the tissue. The major actors of non‐histaminergic itch (PAR‐2, thymic stromal lymphopoietin [TSLP], TSLP‐R, TRPA1 and TRPV1) were expressed in neurons and/or epidermal cells of skin explants. After topical exposure of TRPV1‐(Capsaicin), TRPA1‐(Polygodial) and PAR2‐agonist (SLIGKV‐NH2) activation of reinnervating neurons could be shown in patch‐clamp analysis. The release of TSLP was increased with capsaicin or SLIGKV but decreased with polygodial. Release of CGRP was increased by capsaicin and polygodial but decreased with SLIGKV. Activation by SLIGKV showed a decrease of VEGF; polygodial induced an increase of TSLP, Tumour necrosis factor (TNF) and nerve growth factor and capsaicin lead to a decrease of sema3 and TNF expression. Conclusion The present model is suitable for studying itch and neurogenic inflammation pathways in vitro. We observed that activation of TRPV1, TRPA1 and PAR‐2 leads to different response profiles in re‐innervated skin explants.